Experimental validation of a hybrid converter with enhanced switching ripple cancellation - Papadopoulos, Savvas; Klumpner, Christian; Rashed, Mohamed; Wheeler, Patrick (IET, 2016)
This study presents the experimental evaluation of a proposed new three phase hybrid converter topology for medium voltage applications. The topology is based on the interconnection of a low switching frequency voltage source inverter (VSI), rated at medium voltage, with a high switching frequency low-power rated current source inverter (CSI). The main function of the shunt connected CSI is to cancel the large switching current ripple produced by the VSI while operating at a reduced fundamental voltage enabled by the use of series connected capacitors. The simulations and design procedure outline the possibility of achieving high output grid current quality whilst the added installed power by the CSI remains at <4% compared with the VSI. The experimental results show good correlation between analytical simulated targets of 20% maximum CSI voltage stress albeit with added installed power of 6.7% due to a larger amount of current ripple processed.